Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 6 - Algebra: Equations and Inequalities - 6.1 Algebraic Expressions and Formulas - Exercise Set 6.1: 28

Answer

-19

Work Step by Step

Given -6$x^{2}$ - 11x -17, x=-2 Step 1: Put the value of x=-2 for each x in the expression =-6$(-2)^{2}$ - 11(-2) -17 Step 2: Evaluate the exponential expression$(-2)^{2}$ = (-2)(-2) = 4 =-6( 4)-11(-2)-17 Step 3: Multiply -6(4) = -24 and 11(-2)= -22 =-24 +22 -17 Step 4: Add and Subtract from left to right first add -24+22 -2-17 subtract -19
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.